Understanding global trends in maternal mortality (2013)
Reports that although maternal deaths are preventable, maternal mortality remains high in many developing countries. Notes that the estimated annual rate of decline fell short of the level needed to meet the MDG 5 target, it was much faster than had been thought previously.
Keywords: MATERNAL MORTALITY